Menstrual Hygiene and Sanitation Practices Among Female College Students in Surkhet - Upadhya Adhikari, Shanta (Pragyaratna प्रज्ञारत्न, 2024)
Menstrual hygiene and sanitation practices embodies the importance of menstrual hygiene and sanitation for the health and well-being of individuals who menstruate. Inadequate menstrual hygiene management can lead to health issues, social stigma, and absenteeism from work or school. The objective of this study is to examine the menstrual hygiene and sanitation practices to the help of supportive requirements of campus level girls students. Using quantitative and descriptive methods, the study surveyed 340 out of 2,294 bachelor-level female students at Surkhet Multiple Campus, selected through sample random sampling. Closed ended questionnaire was the tool of this study. The findings emphasize that menstrual hygiene and sanitation practices, along with supportive requirements, are crucial for enhancing menstrual health and overall well-being. When the symptoms of menstruation appear, the majority of respondents (91%) carry a menstrual pad, indicating that they are aware of their menstrual management and also (88%) claimed that both reusable cloth pad and sanitary pad is used for their menstrual hygiene management.